Soil Investigation Analysis Using Drilling and Standard Penetration Test (SPT) Methods at Blang Mane Bridge - Julsena; Usrina, Nura; Sarana, David; Fithra, Herman; Afra, Liza (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
Soil investigation is a fundamental process in geotechnical engineering to assess subsurface conditions for construction projects. This study focuses on the experimental site at Blang Mane, where a borehole designated as BH-01 was drilled to evaluate soil stratification and properties. The investigation aimed to characterize the soil layers through drilling, sampling, and laboratory testing, including Standard Penetration Tests (SPT), to determine geotechnical parameters essential for foundation design.. The surface soil layer at Borehole (BH-01) location consists of 1.0 m of medium-dense gravelly sand. From 1.0 to 3.5 m depth, a layer of silty clay with medium to stiff/hard consistency is observed. Between 3.5 and 10.5 m lies a very dense sand layer, underlain by medium-dense silty clay at 10.5–12.5 m. A medium-dense sandy silt layer extends from 12.5 to 24.0 m, followed by medium-dense sand at 26.0–30.0 m. A very dense sand layer occurs at 30.0–32.0 m, transitioning to medium-stiff/hard clayey silt at 32.0–37.0 m. Sandy silt of medium density is present from 37.0 to 47.0 m, while very dense gravelly sand comprises the deepest layer (47.0–60.0 m). The groundwater table (GWT) at BH.01 is located 7.0 m below ground level.